2022
DOI: 10.1002/cssc.202200270
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Surfactant Properties of Glyoxylic Acid‐Functionalized Lignin

Abstract: The amphiphilic chemical structure of native lignin, composed by a hydrophobic aromatic core and hydrophilic hydroxy groups, makes it a promising alternative for the development of bio‐based surface‐active compounds. However, the severe conditions traditionally needed during biomass fractionation make lignin prone to condensation and cause it to lose hydrophilic hydroxy groups in favour of the formation of C−C bonds, ultimately decreasing lignin's abilities to lower surface tension of water/oil mixtures. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
(94 reference statements)
1
18
0
Order By: Relevance
“…We presume that the (hemi)­acetal or ester is formed with not only the hydroxy groups of cellulose but also those of lignin. When birch wood is reacted with glyoxylic acid in the presence of hydrochloric acid, HSQC-NMR analysis showed that the formation of stable acetals allows lignin extraction while preventing condensation and repolymerization reactions . Similarly, the reduced blackening of lignin in this study may be due to prevented condensation and repolymerization reactions.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…We presume that the (hemi)­acetal or ester is formed with not only the hydroxy groups of cellulose but also those of lignin. When birch wood is reacted with glyoxylic acid in the presence of hydrochloric acid, HSQC-NMR analysis showed that the formation of stable acetals allows lignin extraction while preventing condensation and repolymerization reactions . Similarly, the reduced blackening of lignin in this study may be due to prevented condensation and repolymerization reactions.…”
Section: Resultssupporting
confidence: 54%
“…Bubbles were observed in the wood solution, suggesting that the lignin-derived surface-active agent , can possibly induce foamability. The uniform dispersion of the wood in the liquid glyoxylic acid was challenging in the presence of air bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…S4.2). [15,16] We observed that the ratio of TALD/GA introduced in the reactor prior to extraction was linearly correlated with the TALD/GA ratio measured on the lignin after extraction (Figure 1d). We also noticed that the two aldehydes had a similar reactivity and that simply varying the aldehyde quantities introduced during AAF we could precisely and simultaneously control the type and degree of lignin functionalization. )…”
Section: Lignin Extraction and Characterizationmentioning
confidence: 77%
“…[13,14] We also showed that multifunctional aldehydes could be employed to simultaneously extract and functionalize lignin at high yields which could facilitate its use as a surfactant or for further functionalization for use in resins. [15,16] For multiple high-end material applications including soft tissue engineering, the targeted material must not only be biocompatible, but must also present well-defined rheological and other mechanical properties. Such properties are necessary to mimic the surrounding environment in which they are employed, and to ultimately trigger the desired biological responses.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recently, multiple novel biorefinery concepts have attempted to overcome this typical drawback of traditional, carbohydrate-centred biorefining e.g., by preventing lignin recondensation through either catalysis [17][18][19][20][21][22] or protection-group chemistry. [23][24][25] These technologies are generally referred to as lignin-first biorefining. 26,27 One such a promising lignin-first biorefinery concept is reductive catalytic fractionation (RCF).…”
Section: Introductionmentioning
confidence: 99%